2017
DOI: 10.1371/journal.pone.0172949
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping-by-sequencing markers facilitate the identification of quantitative trait loci controlling resistance to Penicillium expansum in Malus sieversii

Abstract: Blue mold caused by Penicillium expansum is the most important postharvest disease of apple worldwide and results in significant financial losses. There are no defined sources of resistance to blue mold in domesticated apple. However, resistance has been described in wild Malus sieversii accessions, including plant introduction (PI)613981. The objective of the present study was to identify the genetic loci controlling resistance to blue mold in this accession. We describe the first quantitative trait loci (QTL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 76 publications
0
43
0
Order By: Relevance
“…This population was genotyped and phenotyped for postharvest resistance to P. expansum over a four–year period with the objective of identifying heritable genetic markers for blue mold resistance. Norelli et al ( 2017 ) identified a quantitative trait locus (QTL) on LG3 of apple, qM– Pe3.1 , that accounts for almost 30% of the observed variation in blue mold resistance in the GMAL4593 mapping population, and determined that resistance at this locus was due to an allele from M. sieversii (PI613981). Another significant QTL for blue mold resistance, qM- Pe 10.1, was identified on LG10 where many ripening-related genes are located (Costa et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…This population was genotyped and phenotyped for postharvest resistance to P. expansum over a four–year period with the objective of identifying heritable genetic markers for blue mold resistance. Norelli et al ( 2017 ) identified a quantitative trait locus (QTL) on LG3 of apple, qM– Pe3.1 , that accounts for almost 30% of the observed variation in blue mold resistance in the GMAL4593 mapping population, and determined that resistance at this locus was due to an allele from M. sieversii (PI613981). Another significant QTL for blue mold resistance, qM- Pe 10.1, was identified on LG10 where many ripening-related genes are located (Costa et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…This difference is consistent with the presence of three positive alleles for farnesene production in the GS parent. Interestingly, one of the two major QTLs for resistance to P. expansum has also been located on LG10 between 73.6 and 81.8 cM in a ‘Royal Gala’ × Malus sieversii population (Norelli et al ., ). The most significant marker detected was at 29 121 625 bp, inside the 95% confidence interval for ( E,E )‐α‐farnesene production, suggesting that variation in MdAFS1 alleles might also underpin the QTL for resistance to P. expansum .…”
Section: Discussionmentioning
confidence: 97%
“…Pronounced resistance against blue mould has never been reported in Malus × domestica cultivars. Two QTLs were, however, recently identified in a seedling progeny from a cross between a blue mould-resistant M. sieversii genotype and the moderately tolerant 'Royal Gala' (Norelli et al, 2017). The most influential of these QTLs, mapped to linkage group 3, is apparently inherited from the resistant M. sieversii parent.…”
Section: Factors Involved In Blue Mould Tolerancementioning
confidence: 98%
“…The commonly observed decline in resistance as the fruit matures (Norelli et al, 2017) may be connected also to changes in SSC and acidity. Previous analyses of fruit from mid-to late-ripening dessert cultivars (similar to the ones used in the present study) show about 10% increase in SSC and 50% decrease in acidity from the first harvest to the last harvest four weeks later (Tahir and Nybom, 2013).…”
Section: Factors Involved In Blue Mould Tolerancementioning
confidence: 99%